Administration Management At Baranti Community Health Center: A Systems Approach Analysis - Nur Hamdah; Sunandar Said; Devy Febrianti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Readiness to use electronic medical records in Indonesia has met the minimum requirements in terms of infrastructure to implement digitalization of medical record data. With RME, patient data can be accessed quickly and accurately, reducing patient waiting time and minimizing recording errors. In addition, RME also allows integration of medical data between health facilities, making it easier to coordinate and refer patients. This research uses a type of field research (Field Research), with a qualitative descriptive approach which aims to describe phenomena that occur in the field in depth and systematically. The research focus in this study is the Electronic Medical Record (RME) application. The informants in this research were technicians or staff responsible for maintenance and technical support of RME, administrative staff (Registration, laboratory, pharmacy, clusters 1,2,3,4, doctors, polyclinics), head of the Baranti health center. Data collection was carried out by observation, interviews and documentation. The research results show that implementing electronic medical records is faster and easier than manual ones because it is easier to find patient data and archiving is simpler, patient complaints appear automatically, and are supported by the Head of the Community Health Center and the Health Service. Several factors that are the main obstacles include limited internet networks, limited computer equipment, and a long initial assessment process. Conclusion The implementation of Electronic Medical Records (RME) at the Baranti Community Health Center has proven to provide a significant increase in the efficiency of the health administration process. The RME system makes it easy to quickly and accurately search and archive patient data, replacing slower and error-prone manual methods. The recording process becomes more complete and structured, and reduces the use of paper and physical storage space, which also supports cost efficiency and is environmentally friendly. However, there are still obstacles that hinder the optimization of RME, such as application features that are incomplete and less flexible, operational times that are sometimes longer than manual, and training that is not evenly distributed for all staff.